Pengaruh Capital Structure, Intellectual Capital, Liquidity Dan Firm Size Terhadap Firm Performance - Velda Mahardika, Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research has a purpose, namely to prove empirically the impact of capital structure, intellectual capital, liquidity and firm size on firm performance. This research used secondary data. This research was selected data with purposive sampling technique. This research was conducted on manufacturing companies listed in Indonesian Stock Exchange (IDX) during the year 2015-2017. The entire sample used in this research is 184 data from manufacturing companies. The research data is processed with SPSS Statistics Version 21. The result of this this research shows that capital structure and intellectual capital has a positive effect and no significant on firm performance. Liquidity and firm size has a positive effect and significant on firm performance